Evaluasi Pelaksanaan Program Percepatan dan Perluasan Pembangunan Infrastruktur Sumber Daya Air di Bidang Irigasi Kecil - Cahyo, Dwi Nur (Magister Pembangunan Wilayah dan Kota,Undip, 2017)
Acceleration and extension of water resources infrastructure development program in small irrigation (P4 ISDA IK) is a program to reduce the burden on poor people's lives as a result of changes in the amount of oil fuel subsidy. Implementation program of P4 ISDA IK simultaneouslyÂ to support national food security programs and efforts to increase economic capacity and social welfare through the empowerment of farming communities in tissue repair of small irrigation in rural areas. This study aimed to evaluate the implementation of the program to the beneficiary of P4 ISDA IK. Analysis of community participation carried out using quantitative methods to search for a number of variables that can be obtained from several reviews of a theory. From that variables then conducted a descriptive analysis of quantitative and analytical weighting. While the analysis of the performance of Water User Associations (P3A) carried out using Importance Performance Analysis methods (IPA). Based on field studies and processing questionnaire the results showed that the level of participation remained at the consultation level. Regarding the performance of P3A showed that performance indicators that are already well is : P3A have Statutes/Bylaws (AD/ART), P3A has a legal entity, there is an integrity pact and the signing of the contract, Ease requirements to receive P4 ISDA IK, Ease of distribution of funds disbursement, the preparatory work, procurement of materials and goods, construction execution.